Development of Mobile Learning-based Edugame on Respiratory System Material to Improve Students' Digital Literacy - Ferlita Kale; Risya Pramana Situmorang; Susanti Pudji Hastuti (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2021)
The purpose of this study aims to develop mobile learning based edugame based on product feasibility and test the effectiveness of mobile learning based Edugame in improving digital literacy in students. The instruments used are tests, questionnaires, and observation sheets. The research subjects were grade XI of Senior High School at Salatiga. This research was carried out through two phases, namely the first phase of developing mobile learning based edugame using the ADDIE model and the second phase testing the mobile learning based Edugame developed to analyze its effectiveness. From the results of the trial find: 1) mobile learning based edugame developed valid with an average value of 82,24% (content expert) good category and 84,02 (media expert) good category, 2) the practicality of mobile learning based Edugame seen from student response questionnaires with a value of 81,25% good category, 3) the effectiveness of mobile learning based Edugame in terms of digital literacy completeness, namely 3,42 very good category